LEGAL REASONABLENESS AND THE NEED FOR A LINGUISTIC APPROACH IN COMPARATIVE CONSTITUTIONAL LAW - PENNICINO, Sara (Comparative Legilinguistics, 2017)
The paper focuses on the concept of reasonableness in several countries, in particular, comparing common and civil law systems. More specifically, it refers to the use of this word in the discourse of the judiciary and especially in the context of constitutional law. In the latter context reasonableness plays a crucial role in conveying values and thus construing “different” constitutionalisms; in fact it enhances the dynamics of the constitutional framework, while leaving the Constitution unaltered. Up to now, constitutional scholarship has devoted attention to the issue of reasonableness as a tool of adjudication (i.e. by including it in the wider framework of scrutiny techniques, such as strict scrutiny versus proportionality). On the contrary, the underlying hypothesis of this paper is that a solid linguistic approach will enhance the understanding of the role reasonableness plays as the quest for minima moralia in constitutional law.